Loss of VHL in RCC Reduces Repair and Alters Cellular Response to Benzo[a]pyrene - Schults, Marten; Oligschlaeger, Yvonne; Godschalk, Roger; van Schooten, Frederik-Jan; Chiu, Roland (Frontiers in Oncology, 2013)
Mutations of the von Hippel-Lindau (VHL) tumor suppressor gene occur in the majority of sporadic renal-cell carcinomas (RCC). Loss of VHL function is associated with stabilization of hypoxia-inducible factor α (HIFα). We and others demonstrated that there is a two-way interaction between the aryl hydrocarbon receptor, which is an important mediator in the metabolic activation and detoxification of carcinogens, and the HIF1-pathway leading to an increased genetic instability when both pathways are simultaneously activated. The aim of this study was to investigate how environmental carcinogens, such as benzo[a]pyrene (BaP), which can be metabolically activated to BaP-7,8-diOH-9,10-epoxide (BPDE) play a role in the etiology of renal-cell carcinomas (RCC). We exposed VHL deficient RCC4 cells, in which HIFα is stabilized regardless of oxygen tension, to 0.1µM BaP for 18 hours. The mutagenic BPDE-DNA adduct levels were increased in HIFα stabilized cells. Using qRT-PCR, we demonstrated that absence of VHL significantly induced the mRNA levels of AhR downstream target CYP1A1. Furthermore, HPLC analysis indicated that loss of VHL increased the concentration of BaP-7,8-dihydroxydiol, the pre-cursor metabolite of BPDE. Interestingly, the capacity to repair BPDE-DNA adducts in the HIFα stabilized RCC4 cells, was markedly reduced. Taken together, these data indicate that loss of VHL affects BaP-mediated genotoxic responses in renal-cell carcinoma and decreases repair capacity.